Potential role of gut-related factors in the pathology of cartilage in osteoarthritis - Ning, Peng; Lin, Shuting; Shi, Yongyan; Liu, Tianjing (Frontiers in Nutrition, 2025)
Osteoarthritis (OA) is a common progressive degenerative disease. Gut microbiota (GM) and their metabolites have been closely associated with the onset, progression, and pathology of OA. GM and their metabolites may influence the cartilage directly, or indirectly by affecting the gut, the immune system, and the endocrine system. They function through classical pathways in cartilage metabolism and novel pathways that have recently been discovered. Some of them have been used as targets for the prevention and treatment of OA. The current study sought to describe the major pathological signaling pathways in OA chondrocytes and the potential role of gut-related factors in these pathways.